Optimizing University Libraries in Palangkaraya City as a Supporting Facility for Independent Campuses - Saputra, Uji; Riady, Yasir (Mitra Palupi, 2024)
Background: Libraries play an essential role by meeting students' needs, offering a variety of library resources, facilitating access to study spaces, managing lending services, and providing information services. Kampus Merdeka is a support and effort to encourage students to obtain a variety of helpful information for their future job prospects. Purpose: This study aims to know extend on how to optimize libraries to facilitate independent campuses. Design and methods: This article uses a qualitative descriptive methodology, utilizing library reference materials as the primary means of data collection and analysis. According to Sugiyono (2018), qualitative research methods are research methods based on philosophy, which are used to research scientific conditions (experiments) where the researcher is the instrument, data collection techniques, and qualitative analysis emphasize meaning. Results: The role of libraries is in line with the government's program for national education, as stated in Law No. 2 of 2003, which states that education is a conscious and planned effort to realize the teaching and learning process so that students actively develop their potential. Optimizing university libraries in the city of Palangkaraya by utilizing information technology can be used as a means of supporting independent campuses to utilize library resources. Steps that university libraries can take to optimize libraries include: 1) Optimizing the use of information technology and 2) Promotion of libraries by utilizing websites and social media networks to improve service quality. Librarians should strive to facilitate as many opportunities as possible for students to develop into competent individuals.